Análise metataxonômica de comunidades microbianas da rizosfera do milho após aplicação de nitrogênio e inoculação com bactérias - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2019)
The use of plant growth promoting bacteria as an alternative to the use of mineral fertilizer is a growing reality in agriculture. Using inadequate mineral fertilizer generates unnecessary costs and highlights the need for a practical and sustainable solution. Bacteria play a key role in plant growth and production by providing the substrates and nutrients needed for healthy growth. Bacteria present in the soil and rhizosphere of plants are known to have the ability to naturally fix nitrogen, as well as other complex processes that are poorly documented due to the difficulty in cultivating such bacteria through traditional laboratory techniques. In this research, were analyzed metagenomic data from the sequencing of the 16S rRNA gene from the maize rhizosphere. The data were generated through a previous experiment where maize seeds with different nitrogen doses were planted and inoculated with different bacteria, totaling 11 treatments in triplicate. This research aims to determine the taxonomy of microorganisms and investigate the impact on bacterial communities present in the maize rhizosphere comparing to the amount of nitrogen applied and inoculated bacteria. We found 28 phyla, 62 classes, 83 orders, 183 families and 582 genus. Libraries that applied 30 kg N / ha without inoculant, 160 kg N / ha without inoculant, and 30 kg N / ha + Azototal inoculated with A. Brasilense AbV5 + AbV6 showed higher richness of microorganisms. Libraries that applied 160 kg N / ha without inoculation and 30kg N / ha + 8121 inoculated with Rhizobium showed higher diversity of microorganisms. At the genus level, the bacteria that are able to promote plant growth are found in libraries that received 0kg, 30kg and 160kg N / ha without inoculants.
Keywords: Inoculante; Nitrogênio; Azospirillum; Metagenômica; 16S rRNA; Inoculant; Nitrogen; Azospirillum; Metagenomic; 16S rRNA.; CNPQ::CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO